(untitled) (Stato, Chiese e pluralismo confessionale, 2012)
Article subjected to peer review SUMMARY: 1. General framework of the applicability of Italian legislation within the Vatican City State - 2. The right to privacy under European and canon law - 3. Applicability and enforceability of the Italian Data Protection Code within the Vatican City State. Abstract: In the Vatican City State no specific laws have been adopted either by the Supreme Pontiff, the Pontifical Commission, or other legitimate Vatican City State authorities in relation to the fundamental right to privacy of natural and legal persons. Canon 220 of the Code of Canon Law refers to the protection of a good reputation and of intimitas, but does not provide for specific or self-contained rules related to personal data protection; it contains only general principles that can (and should) be articulated in more specific regulations. Therefore, it seems feasible that the provisions of the Italian Data Protection Code concerning the processing of personal data and the protection of privacy in the telecommunications sector - as well as any other provision concerning the sector of telecommunications and relevant services, both of landline and mobile networks, in their entirety - should be automatically applicable within the Vatican City State, pursuant to Article 12.1.a.5 of Law no. LXXI on the sources of law of the Vatican City State. Keywords: personal data protection, intimitas, Vatican City State, sources of law